Opportunities and challenges within green spaces during COVID-19: Perspectives of visitors and managers in Maine, USA - Alyssa Soucy; Elizabeth Pellecer Rivera; Natalie Siwek; Lucy Martin; Sarah Jackson; Gabrielle Venne; Augusta Stockman; Sandra De Urioste-Stone (PLoS ONE, 2025)
COVID-19 impacted, and continues to impact, green spaces across the world, altering visitation patterns, and presenting novel management challenges. As COVID-19 has evolved, the long-term implications on communication, management, and conflict as diverse people interact in green spaces remains uncertain. Our work responds to calls to consider diverse perspectives of individuals whose lives intersect with green spaces. Using a qualitative case study methodology, we explored the meanings and experiences of green space managers and visitors in the State of Maine, USA, during the COVID-19 pandemic between May 2021 and July 2023. We triangulated across five research projects including: phenomenological interviews of conservation practitioners, an online questionnaire of staff from a state conservation agency, and three surveys of visitors to green spaces across Maine. Taken together, our results highlight how COVID-19 increased the number and diversity of visitors to green spaces as a result of the outdoor visitation opportunities provided perceived as “safe” during the pandemic. While managers described the benefits from increased visitation on funding and legislative support, they also identified challenges and negative impacts to local ecology as a result of new and greater use. Our results have implications for communication and management for policy makers and natural resource managers who seek to maintain support for conservation goals and address visitor safety and well-being. Managers maintained flexibility in their decision-making to remain nimble and responsive to emerging opportunities and challenges associated with the pandemic. In addition, our results highlight that the scale of change on human behavior from COVID-19 offers a glimpse into what may be possible if that same level of urgency was applied to issues like climate change.